Reptiles in the diet of a Oncorhynchus mykiss (Osteichthyes: Salmonidae) naturalized population in Piedmont (N Italy) - Franco Bernini (Acta Herpetologica, 2006)
The authors report on predation by salmonid fish on some reptile species in two tributaries of the Tanaro river in the Alessandria province (NW Italy). The remains of Podarcis muralis, Anguis fragilis and of an undetermined colubrid of the genus Natrix were found in bromatological analyses performed on 117 Oncorhynchus mykiss specimens. Salmonid predation on herpetofauna once again confirms the alimentary opportunism of these fishes; however, predation is an occasional phenomenon and not a threat to the local reptile populations.